The relationship between organizational characteristics, task characteristics, cultural context and organizational citizenship behaviors. - Asgari, Ali; Silong, Abu Daud; Ahmad, Aminah; Abu Samah, Bahaman (EuroJournals, 2008)
The current study explored the relationship between organizational characteristics, task characteristics, cultural context and organizational citizenship behavior (OCB), that mediated by POS and Trust. Survey data was collected from a sample of 162 employees in five ministries in Putra Jaya city of Malaysia. The results of structural equation modeling showed that the hypothesized model fit the data very well. Perceived organizational support and trust are good mediators between organizational characteristics and OCB. There is a positive and direct relationship between task characteristics and OCB. In cultural context, only power-distance has a direct and positive relationship with OCB, and individualism and collectivism there are non-significant.